The Moderating Role of Audit Quality in the Relationship Between Financial Performance and Firm Value: A Study of Indonesian Banking Companies (2014-2023) - Ahmad Jibrail; Grahita Chandrarin; Prihat Assih (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This study examines the moderating role of audit quality in the relationship between financial performance and firm value in the Indonesian banking sector from 2014 to 2023. Utilizing a quantitative explanatory design with Moderated Regression Analysis (MRA) and Random Effects models, the research analyzes panel data from banking companies listed on the Indonesia Stock Exchange (IDX). The financial performance variables investigated include Return on Assets (ROA), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM), with firm value measured by Price to Book Value (PBV). Audit quality is proxied by the engagement of Big Four accounting firms. The findings indicate that CAR, ROA, and LDR significantly influence firm value. A key discovery is that audit quality significantly moderates these relationships: it strengthens the effect of ROA but weakens the impact of CAR and LDR on firm value, while demonstrating no significant moderating effect on the NIM relationship. The results underscore the critical role of high-quality external audits as a governance mechanism that enhances the credibility of financial reporting, mitigates information asymmetry, and thereby shapes how financial performance is valued by the market.